Trunk strength characteristics of elite Alpine skiers - A comparison with physically active controls - Hildebrandt, C.; Müller, L.; Heisse, C.; Raschner, C. (Journal of Human Kinetics, 2017)
Core muscle imbalances and weak trunk strength are relevant for injury prevention and performance. Information regarding core strength requirements and ideal flexion/extension ratios in alpine skiing is limited. We aimed to compare trunk strength capacities in elite alpine skiers with those of a matched control group. The concentric maximal trunk flexion and extension of 109 elite skiers and 47 active controls were measured at 150°/s in a ballistic mode using the CON-TREX® TP 1000 test system. The relative flexion peak torque was higher in male ski racers (p = 0.003; 2.44 ± 0.30 Nm/kg) than in the controls (2.32 ± 0.42 Nm/kg). The relative peak torque for extension was 4.53 ± 0.65 Nm/kg in ski racers and 4.11 ± 0.52 Nm/kg in the controls (p = 0.001). Female athletes were significantly stronger in both, relative flexion force (p = 0.006; skiers 2.05 ± 0.22 Nm/kg; controls 1.74 ± 0.28 Nm/kg) and relative extension force (p = 0.001; skiers 3.55 ± 0.53 Nm/kg; controls 3.14 ± 0.48 Nm/kg). No significant differences were found in the ratios of flexion to extension forces in females and males. Ski racers are engaged in extensive strength training for both leg and trunk muscles, which explains the higher peak values. Both groups indicated a low ratio from 0.54-0.59, which represents high trunk extensor muscles strength relative to flexor muscles.